Validación de la Guía de manejo eficiente de materiales de construcción - Arce-Anchía, Eida María (Instituto Tecnológico de Costa Rica, 2017)
Costa Rica generates high amounts of construction waste. This country has enough legislation and tools for sustainable waste management but lacks of good mechanisms to monitor and improve construction materials management in order to reduce construction waste generation (Abarca Guerrero, 2014). In other countries, however, they have criteria and controls for construction waste management with the goal to ensure better efficiency and effectiveness in the use of materials to reduce construction waste. The Instituto Tecnológico de Costa Rica and the Cámara Costarricense de la Construcción have developed a guide for the efficient management of construction materials which aims to promote a positive change in the construction sector. This study has the objective to validate the application of this guide through the analysis of two construction projects under development. The methodology of Participatory action-research (PAR) will be applied, using check list, interviews and observation. Specifically, this research aims: To frame each project for establishing a baseline on the efficient management of materials, to identify factors affecting guide implementation, to identify limitations and opportunities for improvement the Guide use and assimilation, to establish the perceptions of employees about the benefits of having applied this guide in its construction projects, to suggest guidelines for improvement Construction Waste Management Plan in Costa Rica. The study concludes: In order to implement the guide it is necessary, previously, to have a basic management system, trained personnel and committed stakeholders and contractors. Perceived benefits includes improvement in order and cleanliness project site, and maximization in the use of resources that reduces waste and leftovers. The main recommendations are to simplify and to illustrate the Guide, to take advantage of the technology to create tools from the guide and training the users to apply them.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2017.
Keywords: Residuos; Construcción; Investigación; Manejo de desechos; Manejo sostenible